Personality Competence Educator and Students Interest in Learning - Abnisa, Almaydza Pratama; Zubairi, Zubairi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this research is to find the relevance of the personality competence of educators with students' interest in learning. The method used in this study is the library method, where the researcher collects data based on library sources relevant to the research. The study results are that the personality competence of Islamic religious education teachers is an essential part of the learning process for students because the educator's personality is all the attitudes and actions of a teacher who shows good traits and personalities that can affect the achievement of learning objectives. As for the personal competence of teachers in the learning process, among others; Be pious and have faith in Allah SWT, believe in yourself, be wise and tolerant, be open and democratic, be patient in carrying out the teaching profession, develop yourself for professional progress, understand the purpose of education, be able to establish relationships between humans, understand your strengths and weaknesses, Be creative and innovative in the workplace. So, a good personality possessed by educators will also have a good impact on increasing student interest in learning, in other words, the better the personality competence of PAI teachers, the better interest in student learning will be.